2022
DOI: 10.1161/jaha.122.026036
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Coronary Plaque Characteristics

Abstract: Background The relationship between gut microbiota and in vivo coronary plaque characteristics has not been reported. This study was conducted to investigate the relationship between gut microbiota and coronary plaque characteristics in patients with coronary artery disease. Methods and Results Patients who underwent both optical coherence tomography and intravascular ultrasound imaging and provided stool and blood specimens were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…On the other hand, after MK-7 intervention, the genera Barnesiella , Paraprevotella , Turicibacter , Anaerofilum , and Dielma were increased in the VK6 group (Fig. 2 D), which have been implicated to be involved in the regulation of the immuno-inflammatory response in human and animal studies [ 40 44 ]. It should be emphasized that the daily intake of vitamin K2 accounts for only 10–25% of the total vitamin K [ 45 , 46 ], and a significant proportion of vitamin K2 intake is produced by the gut microbiota [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, after MK-7 intervention, the genera Barnesiella , Paraprevotella , Turicibacter , Anaerofilum , and Dielma were increased in the VK6 group (Fig. 2 D), which have been implicated to be involved in the regulation of the immuno-inflammatory response in human and animal studies [ 40 44 ]. It should be emphasized that the daily intake of vitamin K2 accounts for only 10–25% of the total vitamin K [ 45 , 46 ], and a significant proportion of vitamin K2 intake is produced by the gut microbiota [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further bacteria composition analysis revealed that drinking water treated with chlorate decreased cecal Dysgonomonas and Providencia abundance. The abundance of Dysgonomonas is positively correlated to the levels of intestinal inflammation/prethrombotic markers ( Nakajima et al, 2022 ). Providencia is also a pathogen, and has been demonstrated to play an etiologic role in acute intestinal diseases as early as 1977 ( Kholodkova et al, 1977 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in Enterobacteriaceae is associated with larger coronary plaque fibrotic area and more severe coronary atherosclerosis [62]. Recent studies have shown a correlation between specific intestinal bacteria (i.e., Dysgonomonas, Paraprevotella, Succinatimonas, and Bacillus) and plaque vulnerability, intended as the presence of a thin-cap fibroatheroma, lipid-rich plaque with necrotic core, macrophages, microvessels, cholesterol crystals, and large plaque burden [63]. Moreover, marked overexpression of TMA-producing intestinal microbial enzymes was observed in patients with coronary artery disease compared with healthy controls [64].…”
Section: Atherosclerosis and Coronary Artery Diseasementioning
confidence: 99%